The Navidad incident : the downfall of Mats Guili - Ikezawa, Natsuki, 1945-.; Birnbaum, Alfred (San Francisco : HaikaSoru, 2012)
In this sweeping magical-realist epic set in the fictional south sea island republic of Navidad, Ikezawa gives his imagination free rein to reinvent the myths of twentieth-century Japan. A delegation of Japanese war veterans pays an official visit to the ex-World War II colony, only to see the Japanese flag burst into flames. The following day, the tour bus, and its passengers, simply vanish. The locals exchange absurd rumors - the bus was last seen attending Catholic mass, the bus must have skipped across the lagoon - but the president suspects a covert gueriila organization is trying to undermine his connections withJapan. Can the real answers to the mystery be found, or will the president have to be content with the surreal answers?'.
Keywords: Magic realism (literature).